Therapeutic Approaches Targeting Protein Aggregation in Amyotrophic Lateral Sclerosis - Malik, Ravinder; Wiedau, Martina (Frontiers in Molecular Neuroscience, 2020)
Amyotrophic lateral sclerosis (ALS) is a debilitating neurodegenerative disease that targets motor neurons in the brain and spinal cord. It leads to gradual loss of motor signals to muscles leading to atrophy and weakness. Most patients do not survive for more that 3-5 years after disease onset. Current ALS treatments provide only a small delay of disease progression. Therefore, it is of utmost importance to explore new therapeutic approaches. One of the major hindrances in achieving this goal is poor understanding of causes of the disease. ALS has complex pathophysiological mechanisms in its genetic and sporadic forms. Protein aggregates are a common hallmark of ALS regardless of cause. Protein aggregates and cellular protein pathways are attractive therapeutic targets in ALS. Here, we provide an overview of compounds in different stages of pharmacological development and their protein pathway targets.